Keystroke dynamics : stepping forward in authentication - Magalhães, Paulo Sérgio Tenreiro (2006)
Authenticating a user is a complex problem in which we depend to provide some level of trust to the Security Proceedings of the Information System and to the Information System itself. Biometric technologies have shown that they are able to provide high rates of accuracy but they also raise many ethical issues. On the other side of the problem, many times authentication must be made without the collaboration of the one being authenticated. Keystroke Dynamics is a biometrical technology that can be used in stealth mode and that doesn’t present any issues to what relates to being intrusive, when used in collaborative mode. Many results have been published but there isn’t any integrative technologies yet.